Polymeric Nanoparticles of FMISO: Are Nano-Radiopharmaceuticals Better Than Conventional Ones? - de Souza Albernaz, Marta; Ferreira de Carvalho Patricio, Beatriz; Weissmuller, Gilberto; Reynaud, Franceline; CH Adamsen, Tom; Santos-Oliveira, Ralph (Current Radiopharmaceuticals, 2012)
Nanotechnology has been the last frontier in the diagnoses and treatment of many diseases, especially in oncology. The use of nanoparticles of radiopharmaceuticals may represent the future of Nuclear Medicine. In this study we developed, characterized and tested polymeric nanoparticles of FMISO (fluoromisonidazole) in a dynamic study of biodistribution. The results of the development as characterization showed that nanoparticles were well obtained with a size range of 300- 500nm and a spherical shape.
Keywords: Nuclear Medicine